The vanishing season - Schaffhausen, Joanna (London : Titan Books, 2018)
A chilling tale of suspense for fans of julia heaberlin
Keywords: Government investigators -- Fiction; Women detectives -- Fiction; Suspense fiction; Mystery fiction